Eksistensi Injak Telur di Tengah Arus Globalisasi pada Masyarakat Kecamatan Rimbo Bujang Kabupaten Tebo - Mega Novalia Monika; Rinel Fitlayeni; Sri Rahayu (STKIP PGRI Sumatera Barat, 2022)
the midst of globalization in the community of Rimbo Bujang District, Tebo Regency. The purpose of this study was to determine the factors that cause the existence of the Tradition of Stamping Eggs in the Middle Flow of Globalization in the Community of Rimbo Bujang District, Tebo Regency. The theory used in this research is Talcot Theory. Person on Structural Functionalism. The type of research used is descriptive qualitative type, using secondary data sources and primary data. With the purposive sampling method, as well as the number of informants as many as 16 people. The data collection techniques in this study used observation, interviews, and documentation techniques, while the unit of analysis in this study was the analysis group using the Miles and Huberman interactive model which consisted of four stages, namely: data collection, data reduction, data presentation, and conclusion drawing. or verification. The subjects of this study were the Dukun Manten, Manten's Parents, and the Bride and Groom in Rimbo Bujang District, Tebo Regency. The results of the research that the authors found that the existence of stamping eggs in the midst of globalization in the community of Rimbo Bujang District, Tebo Regency, Jambi Province, which includes: 3. Tolerance of the surrounding community to carry out marriages according to their respective cultures, 4. The majority of people come from Java